Violencia intrafamiliar y su relación con el rendimiento académico en adolescentes Huamachuco - Arteaga Araujo, Milan (2016)
This research aims to establish the relationship between the level of domestic violence and academic performance in adolescents I.E "César Abraham Vallejo Mendoza" - Huamachuco. According simple random sampling sample was composed of 234 adolescents. The "test of Domestic Violence in Adolescents and record format academic performance instrument was applied to transcribe the average student grades period 2015. The results show that 52.9% of adolescents have high violence a 76.07% de adolescents present Accordingly academic performance .for process, it is concluded that there is highly significant statistical relationship between the level of domestic violence and the level of academic achievement in adolescents.